Given the points below,
![\begin{gathered} (x_1,y_1)=(7,-3) \\ (x_2,y_2)=(4,-8) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nde5s3u5e2arzfedlvuqsusjhsf2nvo6ss.png)
The formula to find the equation of a straight line is given below as,
![(y-y_1)/(x-x_1)=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/3wt52xf3n7hjhwt6qolt0l02t41489sre0.png)
Substituting the variables into the formula of a straight line above,
![\begin{gathered} (y-(-3))/(x-7)=(-8-(-3))/(4-7) \\ (y+3)/(x-7)=(-8+3)/(-3) \\ (y+3)/(x-7)=(-5)/(-3)=(5)/(3) \\ (y+3)/(x-7)=(5)/(3) \\ \text{Crossmultiply} \\ 3(y+3)=5(x-7) \\ 3y+9=5x-35 \\ 5x-3y=35+9 \\ 5x-3y=44 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kmr9ieiiuhswhqvx7mcp40ol9iuhvakc90.png)
The standard form of a straight is given as Ax + By = C
Hence, the answer is 5x -3y = 44